Characterization of Multiferroic Bi2Mn4O10 by Dielectric and Neutron Spectroscopy. Issue 7 (29th January 2019) - Ziegler, Fabian; Köhler, Lennart; Gibhardt, Holger; Gesing, Thorsten M.; Murshed, Mangir M.; Sobolev, Oleg; Piovano, Andrea; Eckold, Götz
Abstract : The low‐temperature behavior of single‐crystalline Bi2 Mn4 O10 is studied using dielectric impedance spectroscopy and inelastic neutron scattering. Several relaxation processes with pronounced anisotropic character can be identified in the frequency range between 1 Hz and 1 MHz for temperatures between 150 and 300 K. The dielectric as well as the mechanical properties are demonstrated close to the anti‐ferromagnetic transition. The static dielectric permittivity yields a small but well‐defined peak at the Néel temperature of (38.3 ± 0.1) K, which is related to the type‐II multiferroic nature of this transition. Spectra of acoustic phonons, on the other hand, do not exhibit any significant temperature‐dependent variation and, hence, there are no indications for a predominant magneto‐elastic coupling associated with this phase transition. Abstract : High‐quality single crystals of Bi2 Mn4 O10 are used to study details of dielectric relaxation processes in the frequency range between 1 Hz and 1 MHz and the dispersion of acoustic phonons. Special emphasis is placed on the anisotropic nature of these phenomena and the characterization of the multiferroic phase transition at 38.3 K.